The Influence of Price Perception and Perceived Product Quality on Consumer Satisfaction of Detergent Brand XYZ in Medan - Julitawaty, Wily; Fenny; Januarty, Widalicin; Taufik, Yusuf; Sjukun (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study investigates the influence of price perception and perceived product quality on customer satisfaction with detergent brand XYZ. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected through a structured questionnaire administered to consumers who regularly use the brand. The measurement model demonstrated acceptable reliability and validity, while the structural model revealed substantial explanatory power, with an R² value of 0.431 for customer satisfaction. The findings indicate that both price perception and perceived product quality significantly and positively influence customer satisfaction. Perceived product quality exhibited the stronger effect, as reflected by higher f-square values and path coefficients. The combined influence of both variables also proved significant, confirming that customer satisfaction is shaped by the interplay of consumers’ value perceptions and product performance assessments. These results highlight the importance for detergent manufacturers to maintain competitive pricing strategies while consistently delivering high product quality. The study concludes with managerial implications and suggests avenues for future research, including expanding the model with additional variables and using more diverse samples to enhance generalizability.